Effect of pressure on tar decomposition activity of different bed materials in biomass gasification conditions. (15th October 2015) - Tuomi, Sanna; Kaisalo, Noora; Simell, Pekka; Kurkela, Esa
Highlights: The tested bed materials were sand, dolomite, MgO, olivine and olivine/kaolin. Dolomite and MgO had the highest tar decomposing activities. The catalytic activities of dolomite and MgO reduced with increasing pressure. Pure olivine was inactive and behaved similarly to sand in laboratory-scale tests. Abstract: The objective of this study was to compare the tar decomposing activity of different bed materials and to investigate the effect of pressure on their activity at pressures up to 10 bar. Gasification experiments were first conducted in an atmospheric pressure bubbling fluidised-bed gasifier, while the influence of pressure was studied in a laboratory-scale fixed-bed reactor with simulated gasification gas. The tested bed materials were sand, dolomite, MgO, olivine A and a 50/50 wt.% mixture of olivine B and kaolin. At atmospheric pressure both in gasification and laboratory-scale experiments, dolomite and MgO were the most active bed materials. In air/steam-blown fluidised-bed gasification conditions, all the studied bed materials were capable of reducing the tar content in reference to the base case sand; the reductions amounted to 87%, 83% and 54% with dolomite, MgO and olivine B/kaolin mixture, respectively. Increasing pressure decreased the tar decomposing activities of dolomite and MgO. On the other hand, higher pressure enhanced thermal tar decomposition reactions over sand and olivine A. In pressurised conditions at 5 bar, the carbonate and oxide forms of dolomite (calcium either as CaCO3 or CaO) had similar activities implying that the observed loss in activity at higher pressures was more attributed to the pressure rather than the calcination.